Two new species of Helicascus (Morosphaeriaceae) from submerged wood in northern Thailand - Luo, Zong-Long; Yang, Jing; Liu, Jian-Kui; Su, Hong-Yan; Bahkali, Ali H.; Hyde, Kevin D. (Phytotaxa, 2016)
Helicascus species from submerged wood in aquatic habitats in northern Thailand were studied based on morphology and analysis of DNA sequence data. Descriptions and illustrations of H. elaterascus and a new species H. chiangraiensis are provided.  H. chiangraiensis is characterized by unilocular ascostromata, fissitunicate asci with a long, narrow and coiled endoascus, ascospores with 2–4 large refractive guttules. The phylogenetic analysis based on combined ITS, LSU and SSU sequence data placed the species in Morosphaeriaceae (Pleosporales).